Unravelling pH-responsive behaviour of Fe 3 O 4 @CNCs-stabilized Pickering emulsions under the influence of magnetic field - Low, Liang Ee; Tey, Beng Ti; Ong, Boon Hoong; Tang, Siah Ying (Elsevier, 2018)
The pH-responsive characteristic of Fe3O4@CNC (MCNC)-stabilized Pickering emulsions (MCNC-PEs) under the influence of an external magnetic field were investigated. The Pickering emulsions were prepared using MCNC nanocomposites as the emulsifier. The results demonstrated that the MCNC-PEs exhibited reversible pH-dependent stability that was affected by the presence of magnetic fields. The MCNC-PE droplets prepared with 0.3 wt% MCNC was observed to be stable in acidic solution (pH 1.5–5.0) but broken down in alkaline medium (pH ≥ 7.5). This phenomenon could be owing to an abrupt change of MCNC wetting properties as resulted by the combined effects of superparamagnetic hysteresis and high solubility of MCNCs in alkaline environment. The formulated emulsion can be cycled between stable and unstable 3 times upon a simple pH variation. The unique pH-dependent stability was, however, not observed in the emulsion systems prepared using 0.5 wt% MCNCs, suggesting that MCNC-PE with higher degree of surface coverage by MCNC particles were highly stable against both pH changes and magnetic field. This study revealed the reversible inter-droplet stability of MCNC-PEs upon changes in pH with the presence of magnetic field, therefore these engineered emulsions could find potential applications in encapsulation and controlled release of pharmaceutically active compounds.